(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Background: Acute myocardial infarction (AMI) remains a global health burden. Early identification of individuals at high risk, particularly those with ≥70% coronary artery stenosis, can facilitate preventive strategies. This systematic review and meta-analysis aimed to evaluate the risk of AMI among patients with critical coronary artery narrowing. Methods: A comprehensive literature search of PubMed, Scopus, Embase, and Cochrane Library was conducted for stud ies published from January 2000 to December 2023. Eligible studies included adults (≥18 years) with angiographically confirmed ≥70% stenosis in at least one major coronary artery and reported AMI incidence. Data were extracted and pooled using a random-effects model. Heterogeneity was assessed using the I² statistic, and risk of bias was evaluated with the Newcastle-Ottawa Scale and the Cochrane RoB tool. PROSPERO Registration: CRD420251075342. Results: Eighteen studies (n=22,456 participants) were included. The pooled relative risk (RR) of developing AMI in patients with ≥70% stenosis was 3.45 (95% CI: 2.88–4.13), with moderate heterogeneity (I² = 48%). Subgroup analysis showed higher risk among patients with multi-vessel disease and diabetics. Funnel plot and Egger’s test (p=0.22) showed no significant publication bias. Conclusion: Patients with critical coronary stenosis are at substantially elevated risk for subsequent AMI. These findings emphasize the need for vigilant monitoring, risk stratification, and aggressive therapeutic in terventions in this high-risk cohort. Future studies should focus on novel biomarkers and predictive models to enhance early detection.